Tax policy : principles and lessons - Boadway, Robin W., 1943-; Cuff, Katherine (Cambridge : Cambridge University Press, 2022)
Tax policies are informed by principles developed in the tax theory and policy literature. This Element surveys the policy lessons that emerge from optimal tax analysis since the 1970s. This Element begins with the evolution of tax policy principles from the comprehensive income approach to the expenditure tax approach to normative tax analysis based on social welfare maximization and recounts key results from the optimal income tax analysis inspired by Mirrlees and extended by Diamond to the extensive margin approach. This Element also emphasizes analytical techniques that yield empirically relevant concepts and show the equity-efficiency trade-off at the heart of tax policy. We also extend the analysis to recent literature incorporating involuntary unemployment, and policies like welfare and unemployment insurance.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Taxation